First report on Odonates from Ghandhamardan Hills, Western Odisha, India - Dash, Suraj Kumar (ENTOMOLOGIA HELLENICA, 2025)
In the present paper we report the first Odonata inventory of Ghandhamardan hills, Western Odisha, India. Surveys were carried out in Nrusinghanath Waterfall and Harishankar Waterfall during April, 1, and April, 2, 2016. We have recorded a total of 23 species of odonates under 19 genera and 8 families based on the photographic evidences. Our survey reported Camacinia gigantea for the first time from Western Odisha, extending its range in central Indian Landscape. Moreover, study father indicates the need of further systematic surveys in this least explored area of Odisha, to find out the actual odonates diversity of this hill range.